Linezolid and fentanyl: An underrecognized drug‐to‐drug interaction. (18th April 2020) - Corsini Campioli, Cristina; Barth, Dylan; Esquer Garrigos, Zerelda; Abu Saleh, Omar; Sohail, Rizwan M.; Sia, Irene G.
Abstract: What is known and objective: Despite its frequent use in clinical practice, fentanyl's pro‐serotonergic effects are underrecognized, especially in combination with linezolid. Life‐threatening reactions can occur. Case summary: We report a case of serotonin syndrome developed shortly after the initiation of linezolid in a 63‐year‐old patient in whom selective serotonin reuptake inhibitor therapy was discontinued for the duration of antibiotic therapy. However, fentanyl transdermal patch treatment was inadvertently continued. Noteworthy, 24 hours following discontinuation of linezolid, the patient experienced complete resolution of symptoms. What is new and conclusion. Fentanyl can increase the intrasynaptic release of serotonin through their effects on y‐amino butyric acid and its phenylpiperidine chemical structure. We illustrate the importance of thorough medication reconciliation and review of all potential drug‐to‐drug interactions when indicating linezolid therapy to ensure patient safety. We believe that our case provides novel observations and insight that could help recognize similar cases in clinical practice.